Uporaba tvorbene umetne inteligentnosti za pripravo znanstvenih objav na področju biomedicine - Blatnik, Sara (Informatica Medica Slovenica, 2024)
Abstract. Recent breakthroughs in generative artificial intelligence have spurred the adoption of new technologies in academic writing. We conducted a systematic review of scientific publications that address the use of generative artificial intelligence tools in the preparation of scientific papers in the field of biomedicine. Our analysis encompassed 35 original research and review articles, leading us to identify three groups of tools that, when used judiciously, streamline the retrieval of relevant scientific literature, facilitate the drafting, creation, and completion of scientific texts, and enable rapid extraction and summarisation of data and information from scientific papers.
Keywords: academic writing; generative artificial intelligence; large language models; tvorbena umetna inteligentnost; veliki jezikovni modeli; znanstveno pisanje